Kurikulum Merdeka : Fleksibilitas Kurikulum bagi Guru dan Siswa - Salsabila Ihda Alfaeni; Masduki Asbari; hilyah sholihah (AGUSPATI RESEARCH INSTITUTA, 2023)
The aim of this study is to find out new ideas and ideas that are applied to the independent curriculum system to create fun education for students and teachers. In this study report, a descriptive qualitative method was used by taking notes because the data source was obtained by listening to the oral narrative from Guru Gembul's YouTube channel entitled